Redistribution and Insurance with Simple Tax Instruments - Sebastian Findeisen; Dominik Sachs (Center for Economic Studies and ifo Institute (CESifo), 2015)
We analyze optimal taxation of labor and capital income in a life-cycle framework with idiosyncratic income risk. We provide a novel decomposition of labor income tax formulas into a redistribution and an insurance component. The latter is independent of the social welfare function and determined by the degree of income risk and risk aversion. The optimal linear capital tax is non-zero and trades off redistribution and insurance against savings distortions. Our quantitative results reveal that the insurance component contributes significantly to optimal labor tax rates and provides an informative lower bound on optimal taxes: even for welfare functions that do not value redistribution, marginal tax rates are positive for all income levels. Optimal capital taxes are significant and yield sizable welfare gains; in particular if labor income taxes are suboptimal.
Keywords: H21; H23; 330; optimal taxation; capital taxation; redistribution; insurance